Reproductive and morphological performance in the stallion in humbang hasundutan distric - Lestari Evangelina Simamora; Hamdan .; Iskandar Sembiring; Ma'ruf Tafsin; Hasnudi . (Universitas Sumatera Utara, 2017)
This study aims to determine the reproduction and morphological performance of the stallion in Humbang Hasundutan Regency. This research was conducted in Humbang Hasundutan Regency and cement test at Livestock Breeding and Animal Feed Siborong-borong on July - August 2017. This research was conducted on 15 adult stallion. Then by using Ms Excel data application in input to know total, mean, standard deviation, coefficient of diversity. The results showed that in the macroscopic test the cement volume has a coefficient of 7.74% diversity. The color obtained is white gray. 75% viscous viscosity, 26% dilute. pH diversity coefficient 6.79%. In the microscopic test that motility has a coefficient of 9.91% diversity. The concentration has a diversity coefficient of 7.74%. 90% Abnormalities Normal, 10% abnormal. Measurements of morphology include coefficient of diversity of head length2,71, head width 4.54%, length of neck 5.04% height of shoulder1,89% of circumference of chest 3.40%, depth of breasts 6.84%, length of body3,765%, height of hip 2.16 %, Hole width3,14%, Scrotum diameter 9.45%. The coefficient of data obtained shows the number below 10 which means the sample data is taken to show a uniform value. The uniforms obtained indicate good quality score values ​​for breeding.